A Case of Severe and Refractory Membranous Nephropathy Associated to Mucous Membrane Pemphigoid - Eric Mereniuk; Laura Sabbah; Jean-Paul Makhzoum (Case Reports in Nephrology)
Primary membranous nephropathy (MN) and mucous membrane pemphigoid (MMP) are two autoimmune conditions with well-defined diagnostic and treatment guidelines. MN has been linked to bullous pemphigoid (BP) in certain case reports, though little is known regarding the association of MN and other bullous diseases. The association of MN and MMP has rarely been described, and very little data exist regarding the treatment of this association. We report a case of severe refractory membranous nephropathy secondary to mucous membrane pemphigoid successfully treated with rituximab. A 35-year-old woman with known MMP was referred to our clinic for new-onset generalized edema and proteinuria. MN was confirmed on renal biopsy. Despite therapy with high-dose systemic glucocorticoids, combined with mycophenolate mofetil, and later azathioprine, nephrotic-range proteinuria persisted even at a daily dose of prednisone of 40 mg. The patient was then started on rituximab infusions, which induced remission of both mucous membrane pemphigoid and membranous glomerulonephritis. This suggests that MN can be secondary to MMP, and rituximab may be useful induce remission in cases that are refractory to standard therapy.